Optimasi Proses Pada Fungsi Pengelolaan Fasilitas Dalam Arsitektur Bisnis Menggunakan TOGAF ADM - Meidiani Juwita Rachmawati; Asti Amalia Nur Fajrillah (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2020)
In this digital era, the expansion of information technology has made IT a way for companies to achieve their goals. Not only helps in the work process but also can be a solution to problems and achieve the company strategies. In the process of implementing IT, design is needed with in-depth analysis in accordance with company conditions. It is intended that IT applied can be a solution, strategy, effective and efficient for the company. The development of IT also encourages manufacturing type companies to continue to grow. In one of the manufacturing companies in Bandung, especially in the Facility Management Function, there are constraints, namely asset control and application needs. This has become the driving force for manufacturing companies to develop IT in their companies. One of the tools for creating information technology that is in line with business goals is to use Enterprise Architecture (EA). Through EA can maximize investment in the use of IT in an organization. In this study, EA design uses The Open Group Architecture Framework (TOGAF ADM). This research was conducted at a manufacturing company in Bandung and focused from the preliminary phase to the business architecture phase, on the Facility Management Function and using the TOGAF ADM framework. This study uses descriptive methods and aims to provide business architecture design as a solution to the facility management function to optimize business processes and by using IT.